Comparisons between chest trunk mobilization with sustained maximum inspiration and flow incentive spirometry on chest expansion, respiratory muscle strength, and functional exercise capacity in patients undergoing video-assisted thoracoscopic surgery - Khanistha Wattanananont; Sasipa Buranapuntalug; Sira Laohathai (Physiotherapy Quarterly)
Introduction Chest trunk mobilization with sustained maximum inspiration (SMI) and flow incentive spirometry (flow IS) are breathing techniques that mostly apply to patients undergoing video-assisted thoracoscopic surgery (VATS). The purpose of this study was to determine the effects of chest trunk mobilization with SMI and flow IS on chest expansion, respiratory muscle strength, and functional exercise capacity in patients undergoing VATS.